Risk factors for cancer and the importance of screening in adult recipients of living-donor kidney transplant - Hiramitsu, Takahisa; Shimamoto, Yuki; Himeno, Tomoki; Hasegawa, Yuki; Futamura, Kenta; Okada, Manabu; Matsuoka, Yutaka; Goto, Norihiko; Ichimori, Toshihiro; Narumi, Shunji; Kobayashi, Takaaki; Uchida, Kazuharu; et al. (Frontiers in Immunology, 2026)
IntroductionThe incidence of cancer after kidney transplantation (KT) increases owing to the use of immunosuppressive (IS) medications, which may lead to death with a functioning graft (DWFG) and reduced long-term graft survival. However, the effect of IS medications, including their blood levels, on cancer development before graft failure remains underexplored.MethodsThis single-center retrospective cohort study involved 1274 living-donor KTs performed between January 2008 and December 2021. Cancer was diagnosed in 141 recipients before graft failure. DWFG and mortality-free survival were compared between recipients with and those without cancer before graft failure. Multivariable Cox regression analysis was used to identify risk factors for cancer. Trough levels of IS medications (calcineurin inhibitors and mycophenolate mofetil) were compared between recipients with and those without cancer. The effect of cancer detection (screening, incidental, or symptomatic) on DWFG was also evaluated.ResultsDWFG and recipient mortality events were more common in the cancer group than in the non-cancer group. A significant risk factor for cancer was older recipient age (P < 0.001; hazard ratio, 1.066). IS medication levels were similar between the cancer and non-cancer groups. Recipients with cancer detected through screening had lower DWFG rates than those with cancer detected incidentally or symptomatically.DiscussionIS medication level was not a significant risk factor for cancer before graft failure. Nevertheless, cancer risk after KT significantly increased both DWFG and recipient mortality rates. Cancer screening may help reduce the incidence of DWFG and recipient mortality associated with cancer.